The role of academic advisors in assisting sociology students Faculty of Social and Political Sciences, University of Riau - Hidir, Achmad; Gea, Yusuf Krisman; Rusmawati, Puput; Fajri, Azzahra Handhika G.; Vitamagistra, Siti Wahyu; Mardatillah, Mardatillah (Privietlab, 2025)
This study aims to analyze the role and interpretation of Sociology students at the Faculty of Social and Political Sciences (FISIP) of Riau University regarding the role of academic advisors (PA). Paradigmatically, Parsons' structural functionalism theory is often identified with a quantitative approach. However, this study consciously employs Parsons' Role Theory as the theoretical framework for qualitative research, as it focuses on the concepts of “role” and “role expectations,” which are relevant for an in-depth exploration from the students' perspective. The method used is a qualitative approach with a descriptive case study design. Primary data were collected through semi-structured in-depth interviews with 2023 sociology students selected purposively. Data analysis used Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion-drawing. The results show that students have diverse interpretations of the role of PA lecturers, which are often adapted to their personal needs and experiences. The main findings reveal a gap between students' role expectations and the role performance they perceive from academic advisors. This study concludes that the implementation of the academic advising system at the Faculty of Social and Political Sciences, University of Riau, has not been fully effective in meeting students' expectations, and further evaluation is needed to bridge this gap between the two.